ANALISIS FAKTOR-FAKTOR MODEL PERILAKU BIG FIVE (EXTRAVERSION, AGREEABLENESS, CONSCIENTIOUSNESS, NEUROTISICM, OPENNESS TO EXPERIENCE) TERHADAP COMPUTER SELF EFFICACY DAN KEPUASAN KERJA GURU SMA – SMK WIJAYA PUTRA SURABAYA - Nurleila Jum'ati; Yulis Setyowati (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
Computer self-efficacy (CSE) and job satisfaction play an vital role in achieving education’s aims not only in general affairs but also in particular goals both in formal education institutions and teacher’s real life. This research intends to (1) analyze the effect of big five behavior model (extraversion, agreeableness, conscientiousness, neurotisicm, openness to experience) toward computer self-efficacy of teachers in SMA – SMK Wijaya Putra Surabaya, (2) analyze the effect of big five behavior model (extraversion, agreeableness, conscientiousness, neurotisicm, openness to experience) toward teacher’s job satisfaction of teachers in SMA – SMK Wijaya Putra Surabaya. It is highly hoped that the research could be a reference for the schools themselves and the stake holders to manage and improve the teachers. The population of this research is teachers in Wijaya Putra Senior High school and Wijaya Putra Vocational High School which is consisted 52 teachers. This research conducts census method with 46 questioners analyzed. Computer self-efficacy data, Teacher’s job satisfaction data is gained through CSE dan MSQ questioners. While Big Five Behavior Model (extraversion, agreeableness, conscientiousness, neurotisicm, openness to experience) is obtained through the scoring Big Five Inventory (BFI). Those data is analyzed qualitatively with double regression technique The findings show that the factors big five behavior model with dimension agreeableness, conscientiousness and openness to experience effect partially while the dimension: extraversion and neuroticism do not influence significantly towards CSE of the teachers. The factors big five behavior model has the impact significantly on CSE of the teachers in stimulate way. In teacher’s job satisfaction, all of the dimensions influence in stimulate way and partially. It shows that dimension of neuroticism in big five behavior model is the dominant variable which affects the teachers’ Computer Self-Efficacy.